Teacher Pedagogical Competence In A Neuroscience Perspective: A Systematic Review And Meta-Analysis - Saiin Saiin; Heman Hiroyuki; Atsushi Kawachi (Journal Neosantara Hybrid Learning, 2023)
This research is a systematic review of the literature that discusses teacher pedagogical competence in a neuroscience perspective. Overview systematically carried out For deepen knowledge, know the results of previous research, and clarify research problems in context pedagogic competence. Overview systematic done with using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method. PRISMA help para writer And researcher in compile A systematic reviews Where contains guidelines for what items must be in an article. Collected literature Derived from articles published in 2018 to 2023. Based on the results of reading whole content text, there is 19 Which made as article selected. Study This try conducted a literature study on teacher pedagogical competence in a neuroscience perspective.